Changes in the Lena River runoff during the Holocene - Polyakova, Yelena I.; Klyuvitkina, Tatyana S.; Novichkova, E. A.; Bauch, Henning A.; Kassens, Heidemarie (Water Resources, 2009)
The spatial and temporal changes in the Lena River runoff over the last 9 thousand years are reconstructed through studying the freshwater microfossils in sediment cores obtained from the Laptev Sea inner shelf immediately adjacent to the Lena delta and subject to the freshening effect of river water inflowing the sea through the main arms of the delta (the Trofimovskaya, Bykovskaya, and Tumatskaya arms), the sediments having been thoroughly AMS (14)C dated. The freshwater species of diatoms (predominantly the river ones) and green algae that enter the shelf with river water served as indicators of river runoff. The reconstruction of paleosalinity of the sea surface water in the regions under study is based on the relationships (established earlier) between the distribution of freshwater diatoms in the surface layers of sediments in the Arctic seas and the gradients of water salinity in summer. Data on variations in the composition of aquatic microfossil associations in sediments and the reconstructed paleosalinity in the regions of the eastern and western paleovalleys of the Lena River are used to determine the main paleohydrologic events that controlled the variations in the Lena runoff into the shelf zone of the Laptev Sea during the Holocene.